Molecular cloning of copper resistance genes from Pseudomonas syringae pv. tomato. - Bender, C L (1987)
A cosmid library of copper-resistant (Cur) Pseudomonas syringae pv. tomato PT23 plasmid DNA was constructed and mobilized into the copper-sensitive recipient P. syringae pv. syringae PS61. One resultant cosmid clone, pCOP1 (46 kilobases), conferred copper resistance. The PT23 Cur gene(s) was located on pCOP1 by subcloning PstI restriction endonuclease fragments of pCOP1 in the broad-host-range vector pRK404. A subclone containing a 4.4-kilobase PstI fragment conferred Cur on PS61. The Cur gene(s) was further located by insertional inactivation with Tn5. A subcloned fragment internal to the Cur determinant on pCOP2 was probed to plasmid and chromosomal DNA of four copper-resistant and three copper-sensitive strains of P. syringae pv. tomato. The probe hybridized to plasmids in resistant strains, but showed no detectable homology to copper-sensitive strains.